ANALISIS PERAN KOMUNIKASI VERBAL DAN NONVERBAL DALAM MENINGKATKAN EFEKTIVITAS KOMUNIKASI BISNIS DI LINGKUNGAN ORGANISASI - Riana Indrasari; Haudzi Alfirdaus; Ummul Khairah; Anang Haris Firmansyah (Journal of Economics and Development, 2026)
This study aims to analyze the role of verbal and nonverbal communication in improving the effectiveness of business communication within organizational environments. Effective communication is an important factor in supporting coordination, decision-making, performance improvement, and the achievement of organizational goals. This study employs a library research method with a descriptive qualitative approach. Data were collected through a review of various scientific sources, including books, journal articles, and academic publications relevant to verbal communication, nonverbal communication, business communication, and organizational communication. The data were analyzed using content analysis techniques to identify the concepts, functions, and roles of both forms of communication in supporting organizational activities. The findings indicate that verbal communication plays a role in conveying information, instructions, and policies clearly and systematically, while nonverbal communication reinforces message meaning through facial expressions, body language, eye contact, tone of voice, and appearance. The integration of verbal and nonverbal communication has been proven to reduce misunderstandings, improve coordination, build trust, strengthen workplace relationships, enhance customer service quality, and increase organizational productivity. In the digital era, organizations need to integrate face-to-face communication with technology-based communication to maintain communication effectiveness. Therefore, the ability to manage verbal and nonverbal communication has become an essential competency in improving business communication effectiveness and supporting organizational success in facing the dynamics of an ever-evolving business environment.